Avicenna Perpective of Learning-Difficulties, Screen-Time, and Emotional-Behavioral Issues in Children with Tuberculosis - Nisaa', Defa Rahmatun; Dz, Abdus Salam; Karim, Abdul; Sambas, Dedi Rachmadi; Ramadhan, Muhammad Fachdi (Faculty of Medicine, Universitas Padjadjaran, 2025)
Pediatric tuberculosis has become a significant issue in Indonesia, affecting physical, mental, social, and educational aspects of the child. This correlational quantitative study aimed to analyze the correlation between learning-difficulties, screen-time, and emotional-behavioral issues of children with tuberculosis from the perspective of Avicenna. Data collection was performed on 68 children aged 5–12 years in Cirebon, Indonesia, during December 2024. Learning-difficulties were assessed using the Collorado Learning Difficulties Questionnaire in mathematics and language proficiency tests, while emotional-behavioral issues were measured using the Pediatric Symptom Checklist-17. Data analysis was then performed using the Spearman-Rank correlation test. Results showed that there was no significant relationship between learning-difficulties and children's emotional-behavioral issues in either language (r=0.56, p>0.05) or mathematics (r=0.212, p>0.05). However, excessive screen-time was significantly associated with emotional-behavioral issues (r=0.63, p<0.05). Avicenna's perspective shows the importance of balancing physical, mental, and spiritual health to support children's development. This study recommends reducing screen-time, providing family support, and integrating spiritual values into health interventions for children with tuberculosis to mitigate the psychosocial impacts of the disease. Thus, a holistic approach grounded in cultural and spiritual values for managing the condition is crucial.